KESANTUNAN TINDAK TUTUR DEDDY CORBUZIER DALAM ACARA HITAM PUTIH DI TRANS7 - Viora, Dwi (Aksara Public, 2017)
The background of this study is the importance of rhetoric by a host in order to obtain information from guest star. A host of spoken and politeness strategies menggunakna speech acts in order to maintain the image and the image of himself he said partners so as to obtain the desired information. This study focuses on spoken and politeness strategies Deddy Corbuzier speech act in the event of Black & White Trans7. The research is a qualitative research with descriptive method. This study uses the instrument in the form of documentation. Data were analyzed by using content analysis (content analysis). The results of this study are as follows. 1) Strategies used Deddy Corbuzeir recalled in Black and White Trans7 event is spoken frankly without further ado, speak with strings attached positive politeness, and speak with strings attached negative politeness. 2) The principle of politeness used Deddy Corbuzier in Black and White Trans7 event is a compliment maxims, maxims sympathy, and maxims deal. Therefore, it can be seen that Deddy Corbuzeir is the host which has its own characteristics in using spoken strategy and speak with partners politeness principle he said.